Evaluation of buffalo milk production in several states of Venezuela - Néstor Simón Montiel-Urdaneta; José Raúl Pérez-González (Revista Científica)
The buffalo is used as an efficient fodder converter in bovine production systems into milk and quality meat. To know the potential of milk production (MP) in Venezuela, a database was evaluated from 1992 to February 2023 from 36 farms (F) in 12 states of Venezuela, corresponding to 182,413 buffaloes, 198,056 lactations, and 1,440,448 milk controls. The factors evaluated were: ecological zone (EZ), farm (F), breed (B): Murrah predominance (Mu), Mediterranean predominance (Me) and undefined crossbreeding (UC), year of study (YS), number of calvings (NC), lactation duration (LD), dry days (DD) and maternal milk production (MMP). Analysis of variance (ANOVA) was used, using the statistical package SAS version 9, 1. The linear additive model used was: